Pengaruh Kepemilikan Mangerial , Debt To Equity Ratio,Kepemilikan Institusioanal Dan Ukuran Perusahaan Terhadap Kinerja Perusahaan - Silvia Dela Agusta; Siti Nurlaela; Purnama Siddi (Politeknik Ganesha Medan, 2022)
The purpose of this study was to analyze KM, DER, KI, firm size and the effect of firm or organizational size on industrial business performance. The sample for this survey includes 26 businesses with a business population of 14 companies. Sampling by purposive sampling. The conclusion of the survey shows that management ratios and firm size have an influence on organizational performance. On the other hand, the amount of the company's debt has no effect on the company's performance. The results of the study indicate that manager ownership has a positive effect on company performance. This means that companies in the manufacturing sector increase manager ownership to improve business performance. DER has a negative and significant effect on company performance. Indeed, this company does not rely on loan funds or loan funds to fulfill its financial integrity because the company often uses internal capital rather than external capital, thus the size of the company's obligations does not affect the size of the business achieved by the company. KI has a negative and significant effect on company performance. Indeed, the size of the shares owned by an organization does not necessarily affect the high and low performance of a company. While the size of the company has an effect on company performance, meaning that the higher the total assets, the lower the financial performance.